EFEKTIVITAS MODEL PEMBELAJARAN PENCAPAIAN KONSEP TERHADAP KEMAMPUAN MENGIDENTIFIKASI DAN MENGELOMPOKKAN KONSEP MATEMATIKA SISWA KELAS RENDAH SD - Erin Yuriani (CV. ADIBA AISHA AMIRA, 2026)
This study aims to determine the effectiveness of the concept achievement learning model on the ability to identify and group mathematical concepts of lower grade elementary school students. The concept achievement learning model developed by Jerome Bruner emphasizes the inductive thinking process through the presentation of examples and non-examples. This study uses a quantitative approach with a quasi-experimental design of the nonequivalent control group design. The subjects were second-grade elementary school students consisting of an experimental class and a control class. The research instrument was a test of the ability to identify and group mathematical concepts. The results showed that there was a significant difference between the experimental class and the control class. Thus, the concept achievement learning model is effective in improving the ability to identify and group mathematical concepts of lower grade elementary school students.